Design and Construction of Certificate Authenticity Verification System Based on ICP Blockchain at Maxy Academy - Febrian Daffa Eka Putra; Dwi Fatrianto Suyatno (Universitas Negeri Surabaya, 2026)
The falsification of competency certificates has become an increasingly serious issue in the digital era, with significant impacts on the credibility of training institutions and the quality of human resources recruited by companies. Maxy Academy, an institution focused on developing digital competencies through online classes and bootcamps, also faces this risk due to the lack of a proper certificate authenticity verification system. This study aims to develop a certificate verification system based on Internet Computer Protocol (ICP) Blockchain that is secure, decentralized, and tamper-proof. The development method used is Rapid Application Development (RAD), which enables fast system development while actively involving users at every stage. The system developed includes features such as certificate uploading, authenticity verification based on file hash, verification history logging, and authentication using Internet Identity. Testing was conducted using 30 sample data, consisting of 15 genuine certificates and 15 counterfeit certificates, with results showing an accuracy rate of 100% based on the Confusion Matrix method. These results demonstrate that the verification system can accurately distinguish between authentic and fake certificates. With this system, Maxy Academy can enhance industry partner trust and reduce the risk of certificate misuse.